The Impact of Digital Innovation Product Utilization in the Form of Augmented Reality on Students' Decision Making in Choosing Soegijapranata Catholic University, with Brand Image as a Mediating Variable - Winan Kristin Tambunan; Ridwan Sanjaya (SISFORMA, 2023)
The purpose of this study was to determine the effect of augmented reality digital innovation product on decisions by intervening brand image. The samples taken were 100 Soegijapranata Semarang Unika students class of 2021. The analysis technique used was path analysis. The results of the study show: 1) there is a positive effect of augmented reality digital innovation product on brand image, 2) there is a positive effect of augmented reality product innovation on decisions, 3) there is a positive effect  of brand image on decisions, 4) augmented reality digital innovation product has an effect on decisions with brand image as intervening variable.